Historical and Cultural Roots in Anil’s Ghost - Shrivastwa, Bimal Kishore (Researcher: A Research Journal of Culture and Society, 2013)
Michael Ondaatje’s Anil's Ghost narrates the forgotten history and cultural root of those who were massacred in the mindless violence of Sri Lankan Civil War, particularly the common and downtrodden people. Presenting the central character, Anil, beyond the mainstream culture, political and social scenarios, Ondaatje confirms his affinity to the unprivileged people. The pain agony of war victims is clearly examined through the reconstruction of skeletons. The suppressed and unidentified past comes into existence which is the best way to renovate native history within the literary text. Ondaatje historicizes those people who exist on the margin of canonical history. With this novel, he gives voice to those who were unheard in the official history, records them in art and literature as Sri Lankan artist, Anand reconstructs statue of Buddha. DOI: http://dx.doi.org/10.3126/researcher.v1i1.8370 Researcher: A Research Journal of Culture and Society Vol.1(1) 2013